A randomised phase II trial of S-1 plus cisplatin versus vinorelbine plus cisplatin with concurrent thoracic radiotherapy for unresectable, locally advanced non-small cell lung cancer: WJOG5008L. Issue 6 (11th September 2018) - Sasaki, Tomonari; Seto, Takashi; Yamanaka, Takeharu; Kunitake, Naonobu; Shimizu, Junichi; Kodaira, Takeshi; Nishio, Makoto; Kozuka, Takuyo; Takahashi, Toshiaki; Harada, Hideyuki; Yoshimura, Naruo; Tsutsumi, Shinichi; et al.
Abstract Background Cisplatin-based chemoradiotherapy is the standard treatment for unresectable, locally advanced non-small-cell lung cancer (NSCLC). This trial evaluated two experimental regimens that combine chemotherapy with concurrent radiotherapy. Methods Eligible patients with unresectable stage III NSCLC were randomised to either the SP arm (S-1 and cisplatin) or VP arm (vinorelbine and cisplatin), with early concurrent thoracic radiotherapy of 60 Gy, comprising 2 Gy per daily fraction. The primary endpoint was the overall survival rate at 2 years (2-year overall survival (OS)) (Study ID: UMIN000002420). Results From September 2009 to September 2012, 112 patients were enroled. Of the 108 eligible patients, the 2-year OS was 75.6% (80% confidence interval (CI), 67–82%) in the SP arm and 68.5% (80% CI: 60–76%) in the VP arm. The hazard ratio (HR) for death between the two arms was 0.85 (0.48–1.49). The median progression-free survival was 14.8 months for the SP arm and 12.3 months for the VP arm with an HR of 0.92 (0.58–1.44). There were four treatment-related deaths in the SP arm and five in the VP arm. Conclusions The null hypotheses for 2-year OS were rejected in both arms. The West Japan Oncology Group will employ the SP arm as the investigational arm in a future phase III study.